Firm Life-Cycle Learning and Misallocation - Feng, Ying (The Review of Economics and Statistics, 2025)
Abstract Dispersion in marginal revenue products of capital (MRPK) across firms may lower aggregate productivity through misallocation. Using firm-level panel data from China, I document that MRPK dispersion decreases substantially with firm age, particularly before age five. Building on this novel fact, I propose a new interpretation of MRPK dispersion as resulting from firm life-cycle learning. To formalize this idea, I develop a quantitative model in which firms learn about their fundamental productivity as they age in a frictional market with endogenous exits. I find that omitting learning can result in considerable overestimation of TFP losses from "distortions" .